2014
DOI: 10.1371/journal.pone.0099696
|View full text |Cite
|
Sign up to set email alerts
|

Self-Relevant Disgust and Self-Harm Urges in Patients with Borderline Personality Disorder and Depression: A Pilot Study with a Newly Designed Psychological Challenge

Abstract: BackgroundBorderline personality disorder (BPD) is a common psychiatric condition associated with self-harm. Self-harm is poorly understood and there is currently no treatment for acute presentations with self-harm urges.ObjectivesBy using a new task (Self-relevant Task; SRT), to explore emotions related to one's own person (PERSON task) and body (BODY task), to study the correlations of these emotions, specifically disgust, with self-harm urge level changes, and to test the task's potential to be developed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 38 publications
1
12
0
Order By: Relevance
“…This may, in turn, lead to increased maladaptive self‐criticism, isolation from social connections and feelings that one does not belong, which are associated with increased risk for suicide‐related behaviours (Fazaa & Page, ; Hooley, Ho, Slater, & Lockshin, ; Van Orden et al, ). Consistent with the predictions, a recent study reported that self‐disgust was associated with increased urges to self‐harm (Abdul‐Hamid, Denman, & Dudas, ). Importantly, no studies or measures, to the authors' knowledge, have been devised to test the hypothesized association between disgust with life and suicidality.…”
supporting
confidence: 64%
“…This may, in turn, lead to increased maladaptive self‐criticism, isolation from social connections and feelings that one does not belong, which are associated with increased risk for suicide‐related behaviours (Fazaa & Page, ; Hooley, Ho, Slater, & Lockshin, ; Van Orden et al, ). Consistent with the predictions, a recent study reported that self‐disgust was associated with increased urges to self‐harm (Abdul‐Hamid, Denman, & Dudas, ). Importantly, no studies or measures, to the authors' knowledge, have been devised to test the hypothesized association between disgust with life and suicidality.…”
supporting
confidence: 64%
“…Similarly, self‐disgust significantly mediated both the relationship between depression and nonsuicidal self‐injury and the relationship between childhood sexual abuse and lifetime self‐injury status (Smith et al, ), suggesting both that adverse life events exert their influence on self‐injury partially through their effects on self‐disgust and that self‐disgust in turn increases the risk of depression following self‐injury. Abdul‐Hamid et al's () experimental study lends further support to the complexity of this relationship. Specifically, when participants reflected on negative aspects of the personality and then their body (by writing a 3‐min free‐narrative on this) and rated both changes in their disgust levels and changes in their self‐harm urges subsequently, more frequent references to disgust terms in participant narratives was significantly related to an increase in urge to self‐harm.…”
Section: Resultsmentioning
confidence: 75%
“…Psychometric measures designed specifically to assess self‐disgust (e.g., Overton et al, ; Schienle, Ille, Sommer, & Arendasy, ) have only recently been developed. In the absence of standardized self‐disgust scales, the most frequently employed measures of self‐disgust have simply involved utilizing visual analogue scales asking individuals to rate the intensity with which they experience self‐disgust (e.g., Abdul‐Hamid, Denman, & Dudas, ; Badour, Bown, Adams, Bunaciu, & Feldner, ; Badour, Ojserkis, McKay, & Feldner, ; Dyer, Feldmann, & Borgmann, ). Such single‐item measures are unlikely to capture the full complexity of a self‐disgust cognitive‐affective schema and may instead capture a more transient but intense self‐disgust emotional reaction.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One study using a questionnaire measure collapsing disgust towards one's physical appearance and personality showed high scores in a small sample of current MDD and other mental health conditions including borderline personality disorder (BPD) [21]. A further recent study separated experimentally induced personal and physical self-disgust and found physical self-disgust to be more relevant in BPD compared with MDD [1]. So far, there has been only our previous pilot study in remitted MDD to probe self-contempt/disgust, a moral form of self-disgust [18].…”
Section: Introductionmentioning
confidence: 99%